44.8k views
3 votes
Solve for x
-2(2x+60) - 2x = -2(1/5x+6)

User Ildelian
by
4.1k points

2 Answers

2 votes

Answer:

x = -135/7 or -19.3 (✿◠‿◠)

User Shubham Tater
by
4.8k points
1 vote

Answer:

x = -135/7 or -19.3 (rounded to the tenths)

Explanation:

-2(2x+60)-2x=-2(1/5x+6)

First Distribute:

−4x+−120+−2x= −2/5 x+−12

Add Like Terms:

-6x-120= -2/5 x-12

Add -2/5x to each side:

−28 /5 x−120=−12

Add 120 to each side:

−28 /5 x =108

Multiply by (5/-28):

x = -135/7 or -19.3

User Pankaj Agrawal
by
4.8k points